Does fluorosis affect the intelligence profile of children? A cross sectional analysis of school children of district Una, Himachal Pradesh, India - Sharma, Piyush; Bhardwaj, Ashok K.; Singh, Mitasha; Kumar, Dinesh; Sharma, Anupriya; Grover, Ashoo (International Journal Of Community Medicine And Public Health, 2018)
Background: The sub Himalayan region of the country does not fall in highly endemic region for fluorosis. Researchers over the world have hypothesized that high fluoride level in water is the cause of low intelligence level among children and adolescents. We aim to establish the association of high and low fluoride levels with intelligence level and oral health status of children aged 10-14 years in district Una, Himachal Pradesh. Methods: The study was conducted in randomly selected 15 government high schools of district Una. Study population included 600 students of government run schools in age group 10-14years. This ICMR funded project was carried out from 2014 through 2017. Dean fluorosis index was used to study fluorosis level and Intelligence test was conducted on students by using Raven’s standard progressive matrices questionnaire. Results: The 60% of sites studied for fluoride levels were found to have >0.5 ppm fluoride level in water and none of them with level more than 1 ppm. Prevalence of dental fluorosis was 12.2%. Dental caries and high Dental Aesthetic Index were positively associated with high fluoride level in water. Low intelligence level of adolescents was not significantly associated with high fluoride level (OR;95% CI: 1.34; 0.72-2.49). Conclusions: This sub Himalayan region is not endemic for fluorosis however lower level of fluoride is observed in many sites. Fluorosis was not significantly associated with intelligence hence indicating towards multifactorial causation of disease.